Pengaruh Harga dan kualitas pelayanan terhadap perilaku konsumen pada toko rumah kosmetik di Kecamatan Busungbiu - Sari, Putu Monika; Indrayani, Luh (Universitas Pendidikan Ganesha, 2024)
The aim of this research is to determine (1) the influence of price on consumer behavior, (2) the influence of service quality on consumer behavior, and (3) the influence of price and service quality on consumer behavior. The type of research used is causal quantitative research. The sampling technique used was non-probability sampling; the sample for this research was consumers of cosmetic home stores with a sample size of 60. The data collection method used a questionnaire and was analyzed using multiple linear regression. The research results show that (1) there is a negative and significant influence of price on consumer behavior, partially, with a significance value of 0.000 < 0.05. (2) There is a positive and significant influence of service quality on consumer behavior, partially, with a significance value of 0.003 < 0.05. (3) There is a positive and significant influence between price and service quality on consumer behavior simultaneously, with a significance value of 0.000 < 0.05.